2022
DOI: 10.3390/polym15010109
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Organic Pollutant Removal Efficiency of Electrospun NiTiO3/TiO2-Decorated Carbon Nanofibers

Abstract: A nanocomposite comprised of nickel titanate/titania nanoparticles decorated with carbon nanofibers (NiTiO3/TiO2-decorated CNFs) is successfully synthesized via electrospinning and further utilized for methylene blue (MB) photodegradation. The morphology, phase, structural and chemical composition of the nanocomposite is investigated via scanning electron microscope, X-ray diffraction and transmission electron microscope equipped with energy dispersive X-ray. A mathematical model is developed to predict the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Carbon-like graphite, which develops as a result of a partial degradation of carbon during the calcination process, has an outside peak at a 2θ that agrees with (002). The XRD of TiO 2 @CNFs has been shown in our previous work [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carbon-like graphite, which develops as a result of a partial degradation of carbon during the calcination process, has an outside peak at a 2θ that agrees with (002). The XRD of TiO 2 @CNFs has been shown in our previous work [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The catalyst‘s effectiveness is shown to be superior to others previously reported. The catalyst is recyclable and provides a low‐cost solution for wastewater pollution problems [13a] . TiO 2 /activated carbon (TiO 2 /AC) was prepared using the sol‐gel method, and the effect of post‐annealing temperature on its properties and photocatalytic activity was studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that each year about 280,000 tons of textile dyes are released into industrial wastewater by the textile industry [14]. In general, it is thought that throughout the industrial processes, roughly 12% of the total generated synthetic dyes, including methyl orange (MO), methyl red (MR), methylene blue (MB), rhodamine B (RhB), remazol brilliant blue (RB), congo red (CR), and many others, are lost [3,15]. Additionally, 15-20% of global dye production is wasted during the dying process and released into water without additional treatment, resulting in significant environmental damage [16].…”
Section: Introductionmentioning
confidence: 99%